Uma formulação de Petrov-Galerkin para problemas de dispersão pelo método dos elementos finitos - Quezada Celedon, Julian Hermogenes (1988)
This thesis consists in the discussion of a finite element formulation for the difusion-convection equation, using a Petrov-Galerkin scheme with discontinuous weighting functions. This scheme, known as SUPG, introduces the concept of a consistent upwind, that can be easily applied to transient and/or multidimensional problems. Numerical one and two-dirnensional tests are presented to illustrate the main characteristics of the correction method. Results are compared to the solutions obtained by other formulations. It can be concluded, based in the test results, that the proposed correction possesses several advantages which justify its utilization in practical dispersion studies.